Peningkatan Minat dan Hasil Belajar dengan Model Pembelajaran Jigsaw Materi Pokok Barisan dan Deret Bilangan Siswa Kelas IX - Muhammad Bahrun (Cakrawala: Jurnal Pendidikan, 2018)
This research was an action research to improve student’s interest and achievement in mathematics class of IX E SMP N 2 Tarub academic year 2015/2016 trough cooperative learning model jigsaw type. This research was done trough 2 cycles consisted 4 steps; planning, action, observation and reflection. The result revealed that the student’s percentage of interest was good and it was 72.2% in cycle I and 86.1% in cycle II. Based on the result, it could be concluded that cooperative learning model jigsaw type was proved to improve student’s interest and achivement.